Characterization of H7N9 avian influenza viruses isolated from duck meat products. Issue 2 (6th November 2019) - Wu, Li; Mitake, Hiromichi; Kiso, Maki; Ito, Mutsumi; Iwatsuki‐Hirimoto, Kiyoko; Yamayoshi, Seiya; Lopes, Tiago J. S.; Feng, Huapeng; Sumiyoshi, Riho; Shibata, Akihiro; Osaka, Hiroyuki; Imai, Masaki; et al.
Abstract: Avian influenza H7N9 viruses have caused five epidemic waves of human infections since the first human cases were reported in 2013. In 2016, the initial low pathogenic avian influenza (LPAI) H7N9 viruses became highly pathogenic, acquiring multi‐basic amino acids at the haemagglutinin cleavage site. These highly pathogenic avian influenza (HPAI) H7N9 viruses have been detected in poultry and humans in China, causing concerns of a serious threat to global public health. In Japan, both HPAI and LPAI H7N9 viruses were isolated from duck meat products carried illegally and relinquished voluntarily at the border by passengers on flights from China to Japan between 2016 and 2017. Some of the LPAI and HPAI H7N9 viruses detected at the border in Japan were characterized previously in chickens and ducks; however, their pathogenicity and replicative ability in mammals remain unknown. In this study, we assessed the biological features of two HPAI H7N9 virus isolates [A/duck/Japan/AQ‐HE29‐22/2017 (HE29‐22) and A/duck/Japan/AQ‐HE29‐52/2017 (HE29‐52); both of these viruses were isolated from duck meat at the border)] and an LPAI H7N9 virus isolate [A/duck/Japan/AQ‐HE28‐3/2016 (HE28‐3)] in mice and ferrets. In mice, HE29‐52 was more pathogenic than HE29‐22 and HE28‐3. In ferrets, the two HPAI virus isolates replicated more efficiently in the lower respiratory tract of the animals than did the LPAI virus isolate. Our results indicate that HPAI H7N9 viruses with the potential to cause severe diseases in mammals have been illegally introduced to Japan.